2014
DOI: 10.1007/s11239-014-1110-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischemic stroke patients with diabetes should not be excluded from intravenous thrombolysis

Abstract: The benefit of intravenous thrombolysis (IVT) has been questioned for patients with diabetes mellitus (DM) in cases of acute ischemic stroke (IS). Our objective was to analyze the differences in outcome according to prior diagnosis of DM and the use or not of IVT. Observational study with inclusion of consecutive IS patients admitted to an stroke unit. Demographic data, vascular risk factors, comorbidity, stroke severity and 3-month follow-up outcome (modified Rankin Scale) were compared according to prior dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Although not part of our original hypothesis, we found that people with diabetes were significantly less likely to receive tPA treatment than people without diabetes, consistent with findings from other studies [30,31]. A possible explanation for this is that differences in eligibility for tPA treatment existed for those with and without diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although not part of our original hypothesis, we found that people with diabetes were significantly less likely to receive tPA treatment than people without diabetes, consistent with findings from other studies [30,31]. A possible explanation for this is that differences in eligibility for tPA treatment existed for those with and without diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation for this is that differences in eligibility for tPA treatment existed for those with and without diabetes. Alternatively, there may be physician concern about an increased risk of haemorrhage in people with diabetes after tPA treatment [31]; however, it has been shown that tPA improves outcomes in people with diabetes [30]. Therefore, improving thrombolytic treatment in eligible people with diabetes who experience stroke should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombolysis is known to produce better outcomes in stroke patients when compared with diabetic stroke patients [6], and clinical trials [10] did not suggest the withholding of thrombolysis therapy from diabetic stroke patients [11]. Moreover, existing studies suggest that the lower rate of thrombolysis therapy in diabetic stroke patients does not appear to be related to contraindications for thrombolysis because a comparison of contraindications for thrombolysis between ischemic stroke patients with and without diabetes did not reveal a significant difference [12].…”
Section: Introductionmentioning
confidence: 99%
“…44 This highlights the need for comprehensive and tailored management of patients with diabetes during the pandemic and beyond, 43 as well as in stroke patients with pre-existing diabetes who are at risk of poor outcomes after AIS. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]…”
Section: Discussionmentioning
confidence: 99%